Analisis Dana Kampanye Calon Terpilih Anggota Dewan Perwakilan Daerah (DPD) pada Pemilu Serentak 2019 - Novendi Arkham Mubtadi; Syamsul Arifin (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2020)
This article wants to answer about how the amount and nominal budget of elected DPD candidates can be utilized for the effort to win seats for each elected candidate. This study takes a sample of all members of the DPD elected from the existing participation of 34 provinces in Indonesia. The type of data taken in the form of secondary data downloaded from the official KPU website consists of a Report on the Revenue and Expenditure of Campaign Funds. Based on the results of this study, there are two interesting things related to the funding of the DPD in the 2019 Concurrent Elections ago. First, there is no strong relationship when the campaign budget is large. The pair of elected DPD candidates can win seats at a relatively small campaign cost. Second, the amount and amount of campaign costs incurred by prospective DPD members varies. The campaign expenses spent by Adilla Azis from East Java amounted to IDR 75,000. Meanwhile, Jimly As-Shiddiqie from DKI Jakarta spent the largest cost of IDR 1,908,605,402. The average selected candidate issues an average price range of IDR 400 million with an average cost/vote of IDR 3,500.